The long-term effects of the fenestration in patients with extracardiac Fontan circulation—a multicenter Korean cohort study based on national Fontan registry - Ko, Hoon; Song, Jinyoung; Chi, Sang Ah; Lee, Sang-Yun; Kim, Soo-Jin; Lee, Chang-Ha; Park, Chun Soo; Choi, Eun Seok; An, Hyo Soon; Kang, I. Seok; Yoon, Ja Kyoung; Baek, Jae-Suk; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: The long-term effects of fenestration in patients with Fontan circulation remain unclear. We aim to evaluate the fenestration impact on early and late outcomes in patients with extracardiac Fontan (ECF) using a propensity score matching analysis. Methods: We performed an extensive retrospective multicenter clinical data review of the Korean Fontan registry and included 1233 patients with surgical ECF (779 fenestrated, 454 non-fenestrated). Demographics, baseline, and follow-up data were collected and comprehensively analyzed. Patients were divided into two groups according to the baseline presence or absence of surgical fenestration. Subsequently, patients were sub-divided according to the fenestration status at the last follow-up. Propensity-score matching was performed to account for collected data between the 2 groups using a multistep approach. The primary outcomes were survival and freedom from Fontan failure (FFF). We also looked at postoperative hemodynamics, cardiopulmonary exercise test results, oxygen saturations, and functional status. Results: After propensity-score matching (454 matched pairs), there was no difference in survival or FFF between the 2 groups. However, ECF patients with baseline fenestration had significantly lower oxygen saturation (p=0.001) and lower functional status (p<0.001). Patients with fenestration had significantly longer bypass times, higher postoperative central venous pressure, higher postoperative left atrial pressure, and less prolonged pleural effusion in the early postoperative period. The propensity score matching according to the fenestration status at the last follow-up (148 matched pairs) showed that patients with a persistent fenestration had significantly lower oxygen saturation levels (p<0.001). However there were no intergroup differences in the functional status, survival and FFF. Conclusions: Our results showed no long-term benefits of the Fenestration in terms of survival and FFF. Patients with persistent fenestration showed oxygen desaturation but no difference in exercise intolerance was shown between the 2 groups.